A GENERAL MESH SMOOTHING METHOD USING SINGULAR VALUE DECOMPOSITION - Durand, Raul; Oliveira, Vicente (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The elements geometry in finite element meshes can be enhanced by means of mesh smoothing procedures. This paper present a smoothing technique based on the concept of ideal shapes for finite elements and the use of finite element deformation analyses. The ideal shape for a particular element corresponds to a regular shape with the same area or volume. This ideal element is optimally placed over the original one. Assuming a given mechanical stiffness for an element, the resulting nodal points distances between the original and new shapes are used to calculate the forces required to deform the original shape into the ideal one. The forces collected from all elements using this procedure are applied as boundary conditions in a conventional finite element analysis. The results provide a deformed mesh where the elements show improved quality. The whole process can be applied iteratively to get better improvements, however, this technique shows that few iterations are enough to obtain significant enhancement.